IMPLEMENTASI MEDIA PAPAN HITUNG GEHI UNTUK MENINGKATKAN KEMAMPUAN MENJUMLAH DAN MENGURANG POLA BERSUSUN KEBAWAH PADA ANAK HAMBATAN INTELEKTUAL KELAS 4 SD - Tarjiah, Indina; Supena, Asep; Pahlawaty, Neddyana; Ningsih, Kholifatul Novita; Damanik, Prince Clinton Immanuel Christian (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Children with intellectual disabilities often have difficulty understanding abstract concepts, including basic arithmetic operations in mathematics.  A Learning media was designed to bridge the gap in abstract understanding through a visual and interactive approach. The method used is research and development (RD) with the Hannafin Peck model through three stages: needs assessment, design, and development and implementation. The results of the implementation of learning media in the form of GeHi calculation boards as visual-interactive tools in basic mathematics learning for fourth-grade children with intellectual disabilities showed an increase in the ability to add and subtract with results below 100. This is shown by the improvement in the abilities of the four students, such as: increased motivation to learn mathematics, ability to order numbers from smallest to largest and vice versa, ability to distinguish and name numbers (units, tens, and hundreds) based on color coding, and ability to explain the steps of addition and subtraction using the downward pattern using the GeHi counting board.